Fosse Verdon [videorecording (DVD)] - Kail, Thomas, 1978-; Bernstein, Adam, 1960-; Rockwell, Sam; Williams, Michelle, 1980-; Butz, Norbert Leo; Wasson, Sam (Twentieth Century Fox Home Entertainment, 2019)
Drama exploring the marriage and creative partnership between Bob Fosse and Gwen Verdon over five decades.